Health indicators of workers of the hospital area. - de Lima Santana, Leni; Mansano Sarquis, Leila Maria; D'Almeida Miranda, Fernanda Moura; Puchalski Kalinke, Luciana; Andres Felli, Vanda Elisa; Mininel, Vivian Aline (Revista Brasileira de Enfermagem)
Objective: to analyze the health indicators of workers of hospital area for exposure to workloads, wear processes and its consequences. Method: a retrospective, descriptive and exploratory study performed in a hospital in southern Brazil. The population consisted of 1,050 workers notifications of registered in the Monitoring System of Nursing Workers Health, in 2011. Results: 80.8% of the records were female workers, with 34.2% aged between 31 to 40 years old, corresponding to 2478 working lost days. The results subsidized the implementation of nine indicators that showed the prevalence of respiratory and osteoarticular problems. Conclusion: the results allow the reflection and redirection of actions for workers' health, as the processes of becoming ill are compounded by exposure to psychic burdens. These indicators, when monitored, can contribute to the transformation of the profile of morbidity of these workers.